Characterization of corroded anodized coating on titanium, austenitic steel and aluminium base alloy commercially used - Lee, Chee Hong
In this final year project, several techniques used to study the morphological structure as well as characterization of corroded anodized coating of titanium base alloy, austenitic steel and aluminium base alloy commercially used under different service condition and/or environment /medium.